Going digital? The impact of social media marketing on retail website traffic, orders and sales. (May 2021) - Dolega, Les; Rowe, Francisco; Branagan, Emma
Abstract: Given the rapid proliferation of digital technology, social media has become a key digital marketing strategy to promote business products, with the ultimate aim of maximising profits. Yet, empirical evidence on the impact of social media as a marketing tool remains underexplored. Using unique data over a 12-month period from a major online retailer, this paper examines the impact of daily social media activity on daily business outcomes: website traffic, orders and sales. Key findings reveal that social media leads to increased web traffic, but it does not produce a significant rise in product orders and sale income. Though, larger social media campaigns tend to result in significantly higher number of orders and sale income, and Facebook emerges as the most effective channel. Our results also reveal that the effectiveness of social media marketing varies across products depending on their complexity, cost and brand status. Taken together, these results offer a better understanding of the ways social media marketing impact businesses and provide intelligence on how to allocate resources to develop marketing campaigns.